Morpho-physiological characteristics of common bean (phaseolus vulgaris l.) related to drought adaptation (2012)
Development of drought adapted common bean cultivars is a strategy to improve food security in bean producing areas under drought stress. Under greenhouse conditions at the International Center for Tropical Agriculture (CIAT), Palmira, Colombia, we evaluated the morphological and physiological traits of 21 common bean lines (Phaseolus vulgaris L.) that were subjected to drought stress and irrigated treatments using a soil cylinder system. The characteristics evaluated were visual rooting depth, total root length and distribution across the soil profile. In the field, using the same bean genotypes, we evaluated differences in water use efficiency (using carbon isotope discrimination) and grain yield. Under greenhouse conditions, we found that visual rooting depth and root length at soil depth of 60-75 cm correlated positively with shoot biomass (r = 0.56 and 0.50 respectively, P and lt; 0.001) production when water supply was limiting. Under field conditions, grain yield under drought stress was positively associated with carbon isotope discrimination in grain (r = 0.32 P and lt; 0.01). Five lines (NCB 226, SER 16, SEN 56 and SEA 15) had higher root length under drought stress (28, 24, 29 and 27 m/plant respectively) compared with the other lines evaluated, which allows greater water uptake and transpiration, and also in mobilization of photosynthate to greater production of grain. It is estimated that the visual rooting depth, root length at soil depth of 60 to 75 cm and carbon isotope discrimination in grain, are valuable traits as selection criteria in breeding for drought stress tolerance in common bean.